A selection of lower bounds for arithmetic circuits - Kayal, Neeraj; Saptharishi, Ramprasad (Special issue on the occassion of 60th Birthday of Somenath Biswas, 2014)
We survey the problem of proving lower bounds for arithmetic circuits and give an exposition of some of the known lower bounds.